The status of women and its influence on children's well‐being: Do geography, religion and income matter? A comparative study. (24th June 2020) - Panday, Priniti; Rackie, Deanna; Kula, Maria Cornachione
Abstract: Motivation: In most families around the world, women are children's primary caregivers. An improvement in women's status, besides being vital in its own right, has significant positive externalities since the welfare of children has consequences for long‐term economic growth and development. Research question: Could enabling women to have greater opportunities to be productive members of society have a positive relationship with child welfare? Approach and methods: We examine the relationship between women's and children's well‐being for a group of developing countries. We first study this in the context of the overall sample, and then in various country groupings, based on per capita income, geography and religion. A descriptive comparative study and a regression analysis are conducted. Findings and conclusions: We find that women's enhanced well‐being is strongly related to improved child welfare. Although there is a wide variation in women's well‐being within and across various income, geographic and religious groups, our results are robust across and within all groups. In the regression analysis, the only variable that is consistently significant in influencing outcomes for children is our measure of women's well‐being. We cannot reach a clear conclusion regarding the influence of geography, religion and even gross domestic product per capita on child outcomes. Policy implications: It seems imperative for women's empowerment to be a part of every development agenda; a priority in itself, rather than something that should trickle down with overall development. An improvement in women's status, besides being vital in its own right, has significant positive externalities since children's welfare has consequences for long‐term economic growth and development. In our study, it is the single most important factor with a definite impact on children's welfare.